Organizational Change And Organizational Culture Development In A Regional Development Bank In Indonesia - Satya, George Menasye (2011)
The 1997-1998 economic and financial crises in Indonesia have impacted both the public and the private sectors in Indonesia. This crisis has also led to reformation of banking sector in Indonesia which has resulted in the privatizations, mergers and acquisition of a number of banks. In addition, the reform of the banking sector also provided an avenue for Regional Development Banks in Indonesia to change their legal entity to become as limited companies.